Paiches, huanganas e isangos. Repensar el antropoceno a través de la literatura oral y escrita amazónica peruana (Altre Modernità, 2021)
ABSTRACT: Taking as a starting point the considerations of scholars such as Philippe Descola and Boaventura de Sousa Santos on the need to rethink the relations between humans and non-humans in order to seek alternatives to the self-destructive process known by the controversial label of the Anthropocene, it seems appropriate to look at the Amazon rainforest. Indeed, the Amazonian space is “highly transformational” (Rivière), and there is a frequent ontological instability that blurs the boundaries between species. Narratives of animal experiences, for example, are not only used as a symbolisation of some antagonism or social inequality, but are often perceived as realities. In this article, framed in the field of ecocritical studies, a dialogue will be created between some oral stories whose protagonists are animals and the novel by the Peruvian painter and writer César Calvo de Araújo entitled Paiche (1963), which is also the name of one of the largest fish in the Amazonian rivers. Through these creations of oral and written literature, we will reflect on the theme of social inequalities and class consciousness as a means of rethinking how to inhabit the Earth.
Keywords: Paiche; Calvo de Araújo; anthropocene; Peruvian Amazon; animals; ecocriticism